Effect modification of the association between diurnal temperature range and hospitalisations for ischaemic stroke by temperature in Hefei, China. (May 2021) - He, Y.; Tang, C.; Liu, X.; Yu, F.; Wei, Q.; Pan, R.; Yi, W.; Gao, J.; Xu, Z.; Duan, J.; Su, H.
Abstract: Objectives: Diurnal temperature range (DTR) is an important indicator of global climate change. Many epidemiological studies have reported the associations between high DTR and human health. This study investigated the association between DTR and hospitalisations for ischaemic stroke in Hefei, China. Study design: This is an ecological study. Methods: Data of daily hospital admissions for ischaemic stroke and meteorological variables from 1 January 2009 to 31 December 2017 were collected in Hefei, China. A generalised additive model combined with distributed lag non-linear model was used to quantify the effects of DTR on ischaemic stroke. The interactive effect between DTR and temperature was explored with a non-parametric bivariate response surface model. Results: High DTR was associated with hospitalisations for ischaemic stroke. The adverse effect of extremely high DTR (99th percentile [17.1 °C]) occurred after 8 days (relative risk [RR] = 1.021, 95% confidence interval [CI] = 1.002, 1.041) and the maximum effect appeared after 12 days (RR = 1.029, 95% CI = 1.011, 1.046). The overall trend of the effect of DTR on ischaemic stroke was decreasing. In addition, there was a significant interactive effect of high DTR and low temperature on ischaemic stroke. Conclusions: This study suggests that the impact of high DTR should be considered when formulating targeted measures to prevent ischaemic stroke, especially for those days with high DTR and low mean temperature. Graphical abstract: Image 1 Highlights: High DTR was associated with the hospitalisations for ischaemic stroke. The effects of DTR on ischaemic stroke decreased during the entire study period. There is an interactive effect of high DTR and low temperatures on ischaemic stroke.